Can Environmental Cash Transfers Reduce Deforestation and Improve Social Outcomes? A Regression Discontinuity Analysis of Mexico’s National Program (2011-2014) - Alix-Garcia, Jennifer M.; Sims, Katharine R.E.; Orozco-Olvera, Victor Hugo; Costica, Laura; Fernandez Medina, Jorge David; Romo-Monroy, Sofia; Pagiola, Stefano (World Bank, Washington, DC, 2019)
Environmental conditional cash transfers, or "payments for ecosystem services" are a centerpiece of global efforts to protect biodiversity, safeguard watersheds, and mitigate climate change by reducing forest loss. This paper evaluates the impacts of Mexico's national payments for ecosystem services program, which provides five years of payments to landowners in exchange for maintaining and managing natural land cover. Using a regression discontinuity design, the paper studies impacts on environmental, socioeconomic, and social capital outcomes for the 2011-14 program cohorts. The analysis finds that treated communities increased management activities to protect land cover, such as patrolling for illegal conversion or combatting soil erosion (by 48 percent compared to controls). The program reduced the loss of tree cover in areas at high risk of deforestation (by 29 percent compared to controls), with effects being larger for those that have been in the program the longest (38 percent compared to controls). These results are similar to estimates of impact for earlier program cohorts and continue to highlight the importance of targeting the program to areas of high risk of land cover loss to increase environmental effectiveness. The program continued to reach poor communities and households, but estimated impacts on household wealth indicators are small in magnitude and not statistically significant. These results indicate that community-level conditional payments did not harm household-level socioeconomic indicators, a key safeguard requirement of conservation policies of the United Nations Programme on Reducing Emissions from Deforestation and Forest Degradation. The data also show that payments for ecosystem services significantly increased community social capital -- the institutions, attitudes, and values that govern human interactions -- (by 9 percent compared to controls), and these externally provided incentives did not crowd out household contributions to other community work.